Liminality Rituals of Interfaith Families: Symbolic Interactionism and MaqÄshid Sharia Perspectives - Huda, Muhammad Chairul; Muhsin, Ilyya (Ulul Albab: Jurnal Studi dan Penelitian Hukum Islam, 2022)
This study aims to determine the dynamics of life cycle liminality rituals in interfaith families in Salatiga City and their meanings. This study used a qualitative approach with socio-juridical (socio-legal) methods. This fieldwork was conducted on interfaith families in Salatiga City. The results of this study revealed that interfaith marriages in the Salatiga City people, from the perspective of symbolic interactions, involved the mind, self, and society. The actors were influenced by interactions with other individuals and tried to share meaning with society. The cognition construction of interfaith family actors paid attention to the dimensions of society that demand the legality of a marriage. In the ritual act of liminality in the life cycle, interfaith families in Salatiga City had a fairly large tolerance. It was marked by the freedom of family members to perform rituals, whether they came from tradition or religion. In the context of maqÄshid sharia, the concepts of hifdzun nafs, hifdzud dÄ«n, hifdzun nasbi wa nasl, hifdzul mÄl, and hifdzul aql could be maintained as long as there was no coercion from other parties. Thus, freedom of worship and carrying out religious rituals is absolutely necessary.